ESL Teacher Certification Policy: Current Trends and Best Practices - Gras, Christopher; Kitson, Christina (Frontiers in Education, 2021)
Utilizing aspects of the Standards for Initial TESOL Pre-K-12 Teacher Preparation Programs (2018), this study seeks to review and critique current trends in ESL teacher certification policy nationwide. Data collection involved triangulating state policies found online with a brief questionnaire sent to teacher certification boards nationwide (51 in total). The researchers focused on whether or not state policies: (1) offer initial and/or add-on ESL certification; (2) have a test-out option for add-on ESL certification; (3) require a certain number of credits for add-on ESL certification; (4) align their coursework topic requirements with guidelines set forth by TESOL. Data analysis highlighted changes in policy from a previous survey conducted during the NCLB era (Reeves, 2010), and compared requirements in each state’s policy to the Standards for Initial TESOL Pre-K-12 Teacher Preparation Programs (2018). Findings reveal an alarming trend toward less rigorous add-on certification (i.e., endorsement) pathways as well as a number of states either no longer offering initial certification or providing options for testing-out of coursework altogether. Additionally, many state policies outline required coursework, but few follow ESL teacher preparation guidelines set by TESOL International Association (TESOL) (2019). This has led to a notable rift between current ESL teacher education policy and evidence-based best practices such as coursework on the linguistic and cultural aspects of second language learning.